Model Penguatan Penyaluran Zakat kepada Usaha Ultra Mikro melalui Pelatihan dan Pendampingan: Model for Strengthening Zakat Distribution to Ultra Micro Enterprises through Training and Mentoring - Setianingrum, Any; Deviastry, Lily; Nugroho, Randhy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The distribution of zakat to ultra-micro (UMi) business actors, such as Mustahik (people entitled to receive zakat), faces the problem of limited assistance. The Community Service (P2M) aims to minimize failures in the distribution of zakat and ensure that it is used for productive, sustainable, and on-target businesses. The next goal is to increase the quantity and quality of UMi management. The methods used are training, follow-up assistance, monitoring, and evaluation. Partners are UMi actors who receive zakat from the Baitulmal Ummat Islam Foundation Bank Negara Indonesia (BAMUIS BNI). The result of P2M is that previously, there was no assistance in the zakat distribution model. The positive impact is that this assistance increases the accuracy of targeting zakat recipients from the UMi group. This is based on qualitative analysis from the results of interviews with UMi and BAMUIS BNI. The increase in targeting indicates that the Mustahik from UMi are based on recommendations from indigent letters from neighborhood and citizen associations, so they are not concentrated in just a few families, as was the case previously. Another improvement in the distribution model is the absence of brokers, which is often found, unavoidably, without assistance. Another significant impact is that Mustahik receives 100% of the zakat funds directly to the account concerned without any deductions. The mentoring model also equips UMi with various skills training and consultations needed daily to run a business in the era of digital competition. The training includes marketing management, halal production, hygiene, occupational health, and safety.